Design Concept of Tread Compound for Cutting and Chipping Resistance of Truck Tyres on On/Off the Roads - Park, Byung-Ho; Chang, Dong-Ho; Song, Han-Seok; Jung, Il-Taik; Cho, Choon-Tack (Asian Journal of Chemistry, 2013)
Truck tyres, running on and off roads at the same time, commonly observed normal fatigue wear in the initial stages followed by abrasive wear and cutting and chipping later. This study examined many factors that could maintain the initial wear characteristics but prevent cutting and chipping problems on the tread compound of a truck tyre. The physical properties, polymer blends in terms of composition natural rubber base, NR/SBR blend and NR/BR blends, the role of silica in the carbon black base and cure system were investigated. The results showed that it is important to apply the appropriate compound for the actual operating conditions because of the mutual inverse relationship between the wear characteristics and cut and chip properties. The 300 % stress must be at least 90 kgf/cm2 but below 135 kgf/cm2 to prevent blow out as well as provide cut and chip resistance. If 300 % stress is below 90 kgf/cm2, tread compound exhibits low abrasion resistance and frequently experiences blow out under severe conditions. On the other hand, compounds exhibiting a 300 % stress above 145 kgf/cm2 exhibited good fatigue abrasion but poor cut and chip characteristics. In addition to the physical properties, the polymer blend, the cure system and silica loading in a black filled system also showed a trade-off relationship regarding normal abrasion and cutting and chipping resistance.